Author Correction: Long-ranged Cu-based order with $$d_{z^2}$$ d z 2 orbital character at a YBa2Cu3O7/manganite interface - Roxana Gaina (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41535-021-00323-8